Synthesizing factors of the relationship between academic performance and absenteeism among the Diploma of Public Administration students in UiTMCS / Annie Awing Anthony ... [et al.] - Awing Anthony, Annie; Dublin, Connelia; Maring, Julina; Mahli, Azwandy; Mohamad, Tinggal (2004)
Our research topic for this project paper is regarding the factors of the relationship between academic performance and absenteeism among the DPA students’ from part 1 until part 6 of UiTMCS, the reason we conduct this research is because of our awareness regarding their poor academic performance, which also lead to the increase in the rate of absenteeism. This research consists of 5 chapters. For chapter 1 we discussed about the definition of academic performance and absenteeism, the scope of our research study is focusing on DPA students from part 1 until part 6 of UiTMCS. We also discussed about the limitations in conducting this research or the barriers. Overall chapter 1 is about the introduction of our research. Besides that for the literature reviews that we collected from the internet, magazines, journals and newspapers. All of those literature reviews contributed a lot in conducting our research and also helped us in producing questionnaire. Then the method of conducting this research is simple random sampling and we distributed 15 questionnaires to part 1, 21 part 2, 11 for part 3, 16 for part 4, 21 for part 5 and 16 for part 6 students. Besides of all those above, we now come to the findings of our research, where we do it based on the questionnaires we distributed and finally in chapter 5 for recommendation and conclusion, the recommendation comes from us is based on the findings we made and we also concluded the findings we made to answer our objective of conducting this research whether there are relationship between students’ academic performance and absenteeism.